â€œReturn to Edenâ€ : Knowing Christ through Experiencing the Godforsakenness of This World - Sidharta, Leonard (Sekolah Tinggi Teologi Reformed Indonesia, 2020)
Artikel ini berusaha menggali signifikansi soteriologis dari keserupaan dengan Kristus dengan menjadikan konsep kesia-siaan sebagai titik awal pembahasan. Jadi, pembahasan di artikel ini beranjak dari kesia-siaan, yang esensinya adalah ketidakhadiran Allah, menuju keselamatan, yang esensinya ialah kehadiran Allah dengan manusia. Tetapi keselamatan, yang bisa dilukiskan sebagai penawar dari kesia-siaan, justru bekerja lewat kesia-siaan itu sendiri. Dengan kata lain, keselamatan meniadakan kesia-siaan dengan merubah kesia-siaan sebagai kesempatan untuk dipersatukan dengan Allah. Kesia-siaan dapat ditebus, hanya ketika hidup manusia menunjukkan kehadiran Allah didalamnya. Ini sebenarnya adalah hakikat dari kehidupan Kristus di bumi. Di dalam kehidupan Yesus, kejadian-kejadian yang tampaknya sia-sia seharusnya dimengerti sebagai â€œpencobaan,â€ karena hal itu bukan konsekuensi dari nasib, tapi merupakan kesempatan yang dapat memimpin kepada kemenangan (lewat ketaatan) atau kekalahan (lewat ketidaktaatan). This article excavates the soteriological imports of Christlikeness by using the concept of meaninglessness as its starting point. In other words, the article moves from plight (the essence of which is meaninglessness, defined as being without god) to solution, which can be understood as the very antidote to meaninglessness, namely, living with God. However, the antidote works precisely through the meaninglessness itself, that is, it gets rid of meaninglessness by making apparently meaningless happenings into meaningful occasions of being united with God. Hence, one can defeat meaninglessness, only if one manifests Godâ€™s redeeming presence in the midst of oneâ€™s seemingly meaningless life. This is in fact the nature of Christâ€™s life on earth. In Jesusâ€™ life, seemingly meaningless events should be understood as â€œtemptations,â€ as they are not bad fate but occasions that could lead to either victories (via obedience) or defeat (via disobedience).